2016
DOI: 10.5713/ajas.16.0170
|View full text |Cite
|
Sign up to set email alerts
|

A whole genome association study to detect additive and dominant single nucleotide polymorphisms for growth and carcass traits in Korean native cattle, Hanwoo

Abstract: ObjectiveA whole genome association study was conducted to identify single nucleotide polymorphisms (SNPs) with additive and dominant effects for growth and carcass traits in Korean native cattle, Hanwoo.MethodsThe data set comprised 61 sires and their 486 Hanwoo steers that were born between spring of 2005 and fall of 2007. The steers were genotyped with the 35,968 SNPs that were embedded in the Illumina bovine SNP 50K beadchip and six growth and carcass quality traits were measured for the steers. A series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Genomic regions inside or close to the 4w3, 17w4, 20w2, and 27w1 chromosome regions have been previously reported as associated with marbling, fatty acid composition and WBSF ( Cesar et al, 2014 ; Chen et al, 2015 ; Castro et al, 2017 ; Li et al, 2017 ) suggesting that the effect reported on WBSF may be an indirect effect of these genomic regions on meat quality through a direct effect on MARB.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Genomic regions inside or close to the 4w3, 17w4, 20w2, and 27w1 chromosome regions have been previously reported as associated with marbling, fatty acid composition and WBSF ( Cesar et al, 2014 ; Chen et al, 2015 ; Castro et al, 2017 ; Li et al, 2017 ) suggesting that the effect reported on WBSF may be an indirect effect of these genomic regions on meat quality through a direct effect on MARB.…”
Section: Resultsmentioning
confidence: 92%
“…Proteins such as CASKIN2, CDH11, ENSBTAG00000048046, and OGFRL1 are cell proliferation promoters or cell cycle modulators influencing intramuscular and subcutaneous adipocyte proliferation (MARB and FOR). In this regard, several genomic regions inside or close to 2w4, 8w4, 9w1, 14w2, 19w10, 19w4, and 19w8 are associated with FOR and fatty acid composition ( Ishii et al, 2013 ; Saatchi et al, 2013 ; Chen et al, 2015 ; Li et al, 2017 ; Zhu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…No gene with a large genetic effect on this trait was observed, but some chromosomes, such as BTA 14, 3, and 19, had moderate genetic effects on the growth traits. Yi et al [ 16 ] performed a GWAS to detect QTLs affecting growth traits. That study found 16 significant SNPs for weaning weight (WWT) and 18 significant SNPs for 365-d yearling weight (YWT) in Hanwoo.…”
Section: Resultsmentioning
confidence: 99%
“…We simulate a wide range of scenarios under dominant, recessive, and multiplicative models to identify situations where extreme selection strategies should profitably be employed. The enhancement in power is also illustrated through two real data application: the methadone doses (MD) in former heroin addicts undergoing methadone maintenance treatment (MMT) in Israel 10 , and the yearling weight in Korean native beef cattle 11 . Our observations offer a practical guide for researchers to choose an appropriate threshold in defining cases and controls.…”
Section: Introductionmentioning
confidence: 99%